Mihanović Homiliarium in the Monastery of St Prohor of Pčinja: an Overlooked Fragment of a Cognate Serbian Parchment Manuscript Copy of the 14th Century - Темчин, Сергей (Poznańskie Studia Slawistyczne, 2018)
The article presents an analysis of a Cyrillic parchment fragment of Serbian provenance once kept in the monastery of St Prohor of Pčinja and published by J. Hadži-Vasiljević in 1900. The fragment is now identified as belonged to a manuscript copy which had been made from the famous Mihanović Homiliarium. This identification leads to the conclusion that the Mihanović Homiliarium must have been kept in the same monastery of St Prohor of Pčinja already in late 14th c.